Potential opportunities and risks of sharing agricultural research data in Tanzania - Anajoyce Samuel Katabalwa; Jo Bates; Pamela Abbott (IASSIST Quarterly, 2021)
Purpose: The purpose of this paper was to examine the potential opportunities and risks of sharing agricultural research data in Tanzania identified in the existing research literature.